The blockchain: opportunities and challenges for agriculture - Toulon, Nathalie (Technical Centre for Agricultural and Rural Cooperation, 2018)
Nathalie Toulon from the AgroTIC Digital Agriculture Chair in France discusses the many ways in which the blockchain can potentially change agriculture, for example by enhancing trust, transparency and efficiency, and several pitfalls to take into account. Like any new technology, the blockchain should not be viewed as a panacea. For it to serve development, it will need to mature